CHANGED CONVULSIVE SENSITIVITY OF ANIMALS AFTER MILD BRAIN TRAUMA IN CONDITIONS OF GENERALIZED SEIZURE ACTIVITY - Savytskyi І.V.; Frenkel, S.M.; Vastyanov, R.S.; Stoyanov, O.M.; Dobrovolskyi, V.V.; Zayats, L.M.; Vastianov, M.R. (World of Medicine and Biology, 2023)
The purpose of the study was to investigate the change in the intensity of acute generalized convulsive reactions induced by convulsants with different mechanisms of convulsive action during the early posttraumatic period of experimental mild brain trauma. 185 rats were randomized into 5 groups according to the type of convulsant with the help of which the acute generalized convulsive reactions were initiated 6, 12, 24 hours and 3 days after mild brain trauma. A change in convulsive sensitivity was registered within 3 days of the posttraumatic period in the brain of rats which is confirmed by seizure threshold decrease. In case of acute convulsions induction by picrotoxin and pentylenetetrazol their intensity was already higher on the 1st day of posttraumatic period. In case of strychnine-, pilocarpine- and kainic-induced acute generalized seizures the expressed differences were reached on the 3rd day after brain trauma. Convulsive readiness increase and seizure threshold decrease in the dynamics of the posttraumatic period was proved to be a probable pathogenetic mechanism of involuntary self-sustaining seizures occurrence that is the posttraumatic epilepsy clinical basis. The authors believe that obtained results confirm the concept of pathological disintegration of organs and systems in pathological conditions formation which allows us to interpret the pathophysiological mechanisms of traumatic brain damage in mild brain trauma as new type of pathological interaction formation between the cerebral cortex and subcortical formations, which enhances brain convulsive sensitivity including the central GABA-, glycine-, choline-kainate- and monoaminergic neurotransmission participation.